Characteristics and management of pediatric pemphigus vulgaris - LIANG Wenhui, CHEN Yuting, DAN Hongxia (口腔疾病防治)
Pemphigus vulgaris (PV) is the most common subtype of pemphigus. It predominantly affects adults, with pediatric cases being exceedingly rare. Despite advancements in clinical treatment, the mortality rate of pediatric PV (PPV) has historically been alarmingly high, ranging from 70% to 100% in the absence of proper diagnosis and treatment. Although recent improvements in therapeutic strategies have led to a gradual decline in mortality, early and appropriate intervention remains crucial, particularly for children with acute onset and rapid disease progression, to prevent severe complications. However, due to the rarity of PPV, no standardized diagnostic and treatment guidelines are currently available. This study retrospectively analyzed 104 PPV cases recorded in the PubMed and China National Knowledge Infrastructure (CNKI) databases between 1969 and 2024, with the aim of providing insights for the standardized diagnosis and management of PPV. PPV presents with flaccid blisters affecting both cutaneous and mucosal surfaces. Upon rupture, these blisters result in painful, sharply demarcated erythematous erosions, accounting for approximately 1.4%-3.7% of all reported PV cases. The age of onset ranges from 1.5 to 18 years, with an average of 12.4 years, and no significant gender differences have been observed. In pediatric patients, the oral mucosa is typically the earliest and most frequently affected site, with an involvement rate as high as 87.3%, and it most commonly affects the buccal mucosa (27.9%). Other mucosal sites are affected in 52.9% of cases, with genital (28.8%) and perianal (6.7%) involvement being more frequent than in adult patients. Skin lesions are present in 80.4% of pediatric cases, a significantly higher rate than 16.0%-68.4% observed in adults. If lesions are relatively localized, local glucocorticoid therapy can be attempted first, with 8.3% of children achieving complete remission through local treatment alone. Systemic glucocorticoid therapy is the preferred option for cases that respond poorly to local therapy. Among these cases, 75.3% of pediatric patients were treated with prednisone, with 85.1% starting at an oral dose of 0.5-1.5 mg/kg/day, while 14.9% received an initial dose of 2 mg/kg/day. Alternative treatments, such as immunosuppressants, biologics, or other adjuvant medications, may be considered for pediatric patients who exhibit an inadequate response to glucocorticoid therapy or experience severe adverse effects. The most commonly used agents include azathioprine (24.0%), dapsone (21.7%), and rituximab (12.5%). The follow-up period for pediatric patients ranged from 1 to 120 months, with an average duration of 38 months. Prognosis in pediatric patients was more favorable compared to adults, with 43.8% achieving complete remission (cessation of treatment), 37.5% achieving partial remission (low-dose maintenance therapy), 9.6% still undergoing treatment, and only 1.1% succumbing to pneumonia or sepsis. Compared to adults, prolonged corticosteroid use in children poses a greater risk to physiological and psychological well-being, making them more susceptible to adverse effects related to growth, metabolism, and ocular health. Severe adverse reactions occurred in 22.1% of pediatric patients receiving corticosteroids, with Cushingoid facies (73.9%) and weight gain (39.1%) being the most common. In addition, 30.4% experienced growth and skeletal abnormalities, including growth retardation (17.4%), osteoporosis (8.7%), and fractures (4.3%). While PPV shares certain etiological, clinical, and histopathological characteristics with adult PV (APV), early diagnosis and timely intervention remain critical for optimal outcomes. Multidisciplinary collaboration is often necessary to ensure comprehensive management, improve treatment adherence, and safeguard the physical and psychological health of pediatric patients.